Regulated cell death and DAMPs as biomarkers and therapeutic targets in normothermic perfusion of transplant organs. Part 2: implementation strategies - Walter G. Land; Walter G. Land; Walter G. Land; Andreas Linkermann; Andreas Linkermann; Andreas Linkermann (Frontiers in Transplantation)
This Part 2 of a bipartite review commences with the delineation of a conceptual model outlining the fundamental role of injury-induced regulated cell death (RCD) in the release of DAMPs that drive innate immune responses involved in early inflammation-related allograft dysfunction and alloimmune-mediated allograft rejection. In relation to this topic, the focus is on the divergent role of donor and recipient dendritic cells (DCs), which become immunogenic in the presence of DAMPs to regulate alloimmunity, but in the absence of DAMPs acquire tolerogenic properties to promote allotolerance. With respect to this scenario, proposals are then made for leveraging RCD and DAMPs as biomarkers during normothermic regional perfusion (NRP) and normothermic machine perfusion (NMP) of transplant organs from DCD donors, a strategy poised to significantly enhance current policies for assessing donor organ quality. The focus is then on the ambitious goal to target RCD and DAMPs therapeutically during NRP and NMP, aiming to profoundly suppress subsequently early allograft inflammation and alloimmunity in the recipient. This strategic approach seeks to prevent the activation of intragraft innate immune cells including DCs during donor organ reperfusion in the recipient, which is driven by ischemia/reperfusion injury-induced DAMPs. In this context, available inhibitors of various types of RCD, as well as scavengers and inhibitors of DAMPs are highlighted for their promising therapeutic potential in NRP and NMP settings, building on their proven efficacy in other experimental disease models. If successful, this kind of therapeutic intervention should also be considered for application to organs from DBD donors. Finally, drawing on current global insights into the critical role of RCD and DAMPs in driving innate inflammatory and (allo)immune responses, targeting their inhibition and/or prevention during normothermic perfusion of transplant organs from DCD donors - and potentially DBD donors - holds the transformative potential to not only alleviate transplant dysfunction and suppress allograft rejection but also foster allograft tolerance.